Perbedaan Individual dalam Kecerdasan dan Kepribadian - Sutra Awaliyah Darfin; Bunga Rosani; Nur Salsa Nabila; Gizki Maharani; Andi Nilan Sari; Nola Fauziah (Ta'rim: Jurnal Pendidikan dan Anak Usia Dini, 2025)
Individual differences in intelligence and personality have a significant impact on various aspects of life, including academic achievement, social interaction, and professional performance. This study aims to explore the influence of interactions between emotional, cognitive, social intelligence, and personality dimensions on individual success. Based on the five journals reviewed, it was found that both factors influence each other and contribute to achieving positive outcomes in various areas of life. This analysis is expected to provide deeper insight into the importance of intelligence and personality in everyday life.